BBC English Dictionary - British Broadcasting Corporation (London BBC English, HarperCollins Publishers, 1992)
This dictionary is the result of a major partnership between BBC English and Collins Cobuild reflecting the spoken language as used on the BBC World Service. The dictionary includes over 60,000 references, 70,000 examples and 1000 encyclopaedic entries.
Keywords: English language -- Broadcasting